Effect of gamma rays and ethyl methane sulphonate (EMS) on yield and yield attributes of Cicer arietinum in M1 generation - L. Mullainathan; S. Umavathi (Innovations in Agriculture, 2018)
A study was conducted to compare the effect of mutagens on yield and yield attributes of chickpea in M1 generation. In this regard, ‘CO-4’ variety of chickpea was subjected to different concentrations of gamma rays (20, 30, 40, 50 and 60kR) and EMS (10, 20, 30, 40 and 50mM) for inducing mutation. The effect of gamma rays and EMS with different doses/concentrations on yield and yield attributes were observed in M1 generation. From the result, it was observed that the mean value of all the quantitative traits of M1 generation showed a reduction upon enhancing the doses of mutagen. Mean performance in terms of these traits showed good qualities in comparison with the treated plant. The lethal doses were found in 40kR of gamma rays and 30mM of EMS and were carefully analyzed for further generations.